Balancing the banks global lessons from the financial crisis - Dewatripont, M.; Rochet, Jean-Charles; Tirole, Jean (Princeton University Press, 2010)
The financial crisis that began in 2007 in the US swept the world, producing substantial bank failures and forcing unprecedented state aid for the crippled global financial system. This book draws critical lessons from the causes of the crisis and proposes important regulatory reforms.